An accurate and explainable ensemble learning method for carotid plaque prediction in an asymptomatic population. (June 2022) - Wu, Dan; Cui, Guosheng; Huang, Xiaoxiang; Chen, Yining; Liu, Guanzheng; Ren, Lijie; Li, Ye
Highlights: As far as we know, we are the first to assess the carotid plaque occurrence using a machine learning method. High accuracy is achieved in carotid plaque prediction, even when data are missing. The underlying causal reasoning for the machine decisions is explainable, enabling subclinical interventions.The proposed method is a promising tool for large-scale screening of stroke. Abstract: Background and objective: The identification of carotid plaque, one of the most crucial tasks in stroke screening, is of great significance in the assessment of subclinical atherosclerosis and preventing the onset of stroke. However, traditional ultrasound examination is not prevalent or cost-effective for asymptomatic people, particularly low-income individuals in rural areas. Thus, it is necessary to develop an accurate and explainable model for early identification of the risk of plaque prevalence that can help in the primary prevention of stroke. Methods: We developed an ensemble learning method to predict the occurrence of carotid plaques. A dataset comprising 1440 subjects (50% with plaques and 50% without plaques) and ten-fold cross-validation were utilized to evaluate the model performance. Four machine learning methods (extreme gradient boosting (XGBoost), gradient boosting decision tree, random forest, and support vector machine) were evaluated. Subsequently, the interpretability of the XGBoost model, which provided the best performance, was analyzed from three aspects: feature importance, feature effect on prediction model, and feature effect on prediction decision for a specific subject. Results: The XGBoost algorithm provided the best performance (sensitivity: 0.8678, specificity: 0.8592, accuracy: 0.8632, F1 score: 0.8621, area under the curve: 0.8635) in carotid plaque prediction and also had excellent performance under missing data circumstances. Further, interpretability analysis showed that the decisions of the XGBoost model were highly congruent with clinical knowledge. Conclusion: The model results are superior to those of state-of-the-art methods. Thus, it is a promising carotid plaque prediction tool that could be used in the primary prevention of stroke.